Software para la gestión y seguimiento de las obras civiles, accesible desde la WEB para el Ilustre Municipio del cantón Paltas, aplicando la tecnología AJAX. - Criollo Dumas, Amada Alexandra (2010)
The administration of the information and the documentation related with the civil works it is converting day by day in a job that each time is more important and expensive that requires new solutions. These solutions should allow to organize the whole process in the most effective and simple possible way, increasing the productivity and reducing the costs, for such reason; the work named: “Software for the Administration and Pursuit of the Civil Works, accessible from the web for the Illustrious Municipality of the Paltas Canton, applying the Ajax technology”, has as main objective to solve the lack of time for the administration and pursuit of the civil works directed by the personnel of the department of public works, in such way that the activities will be carried out in smaller time and with more efficiency, allowing at the same time to maintain the up-to-dated and unified information and with an easy access. The design of the whole application, as of the Web as the Desk part, follows the orientated paradigm to Objects, being necessary the elaboration of a diagram of use case, diagram of classes, prototype of screens, diagrams of robustness and sequence for each use case, models that were built using the tool of modeling UML, Enterprise Architect. For the design of the database (Diagram Entity- relation), the tool DB Designer was used. For the construction of this application it was used the Seam Framework, created by Jboss, which is easily integrated with other Frameworks, like is the case of RichFaces that was used for the construction of the views; this Framework also allows to create applications that are adapted to the web navigators that exists at the present time. NetBeans, was used like an environment programming, since it is an available IDE in a gratuitous way that offers a complete support for Java, likewise for the manipulation of the Database, the Framework Seam uses a model of very sensitive programming, where all the pojos that is to say a bean (plane object of java) in the classes they are considered as components; in other words, it is model an entity of the business that needs to have persistence. This application contains all related to the generation of budgets, control of projects, and generation of polynomial formula and quadrille type, elaboration of schedules, generation of readjustments, among these and other processes that are carried out in the department of public works. Cabe destacar que esta aplicación está debidamente documentada con los manuales de programador y de usuario para una mejor comprensión, tanto en forma como en diseño. It is necessary to mention that this application is properly documented by means of the programmer and the user manuals, for a better understanding, as much in form as in design.